Sistematización del proceso de sensibilización sobre violencia de género basado en el Teatro del Oprimido realizado por el equipo de promoción de derechos de los Centros de Equidad y Justicia del Distrito Metropolitano de Quito, de febrero a julio del 2017 - Cárdenas Méndez, Jean Paúl (2018)
The present work deals with the systematization of a project of sensitization made it by the area of promotion of rights of the Equity and Justice Centers of the Metropolitan District of Quito and practitioners students of Psychology of the Universidad Politécnica Salesiana, approach that had not been carried out before in the Metropolitan District of Quito, so it was considered important to treat these issues in young people. The theme of the sensitization is gender violence and it was done through the Theaters Forum, based on a theoretical perspective of the Theater of the Oppressed proposed by Augusto Boal, looking to evidence if during sensitization came to meet the psychosocial processes of osmosis, metaxis, analog induction and catharsis. Through a qualitative categorical analysis on the data collected during the experience was concluded that the psychosocial processes posed by the theory were met and achieved an empowerment on the participants on behaviors to change in terms of gender violence.